Analyzing competitive dynamics by crossing geographical scales and organizational levels: An application to the African beer industry - (:unkn) unknown (My University, 2023)
Africa is an important field of direct confrontation between the main players in the world’s beer industry. Our work aims to extend the analysis of competitive dynamics by comparing geographical scales and organizational levels. Based on a collection of secondary data, we will illustrate through this exploratory research five cases of coopetitive actions among the main players in the beer and beverage sectors in Africa. Our results confirm the complexity of competitive situations and the relevance of cross-level analysis. They emphasize the need for a global and multidimensional approach in order to understand competitive dynamics in progress.
Keywords: African Research